Influencia de las formas de financiamiento a corto plazo en el riesgo sistemático de las empresas latinoamericanas - Pires, Paulo Alexandre da Silva (2024)
This research aims at identifying the impact of short-term funding methods of organizations (bank funding or commercial funding) on the systematic risk of Latin American companies. The proposal is based on the ideas provided by Hamada (1972) and Modigliani and Miller’s theory (1958, 1963), evidencing the relationship between the funding structure of companies and the systematic risk. Multiple linear regression econometric models were estimated. The systematic risk was measured by levered beta (β) and the respective disaggregation of unlevered beta (βD) and residual beta (βR). The sample under study belonged to Latin American companies from 2009 to 2022. The main findings evidence a negative relationship between short-term commercial and bank debt and unlevered beta from Latin American companies, resulting in higher intensity and significance for commercial debt. The study includes evidences that contribute to the finance literature by making clear that short-term funding methods impact on the systematic risk of organizations. From the practical contribution perspective, this research explains to market actors and investors that the funding structure determined by operational activities, through operational liabilities, must be considered in the asset pricing process.